Alternative treatments for footwear industry liquid effluents. Part 1 Classic approach - M. J. Ferreira (2002)
The footwear industry generates small volumes of non-biodegradable liquido effluents from finishing operations which have a high organic load, mainly due to pigments, organic acids and organic solvents. In consequence, these effluents must be treated to accomplish regulatory requirements before discharge. One of the treatment alternatives is coagulation/flocculation, a well-known treatment for removing fine particles and colloids. Tests carried out using lime, aluminum sulphate, ferric chloride and ferric sulphate as coagulants gave chemical oxygen demand (COD) and 5-day biochemical oxygen demand (BOD5) removals over 80-90%. However, despite this efficiency, some of the effluent characteristics are still higher than those imposed for discharge to surface waters, land or sewage systems. A polishing step using activated carbon adsorption is then required to permit the discharge to sewage systems, but the quantities of adsorbent required casts some doubt on the feasibility of the process.